2018
DOI: 10.1039/c7fo01654a
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiles of eight olive cultivars from Algeria: effect ofBactrocera oleaeattack

Abstract: Olive fly (Bactrocera oleae R.) is the most harmful pest of olive trees (O. europaea) affecting their fruit development and oil production. Olive fruits have characteristic phenolic compounds, important for plant defense against pathogens and insects, and with many biological activities, they contribute to the high value of this crop. In this study, olives from 8 cultivars (Abani, Aellah, Blanquette de Guelma, Chemlal, Ferkani, Limli, Rougette de Mitidja and Souidi) with different degrees of fly infestation (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Olive fly is the major olive pest in the Mediterranean Basin, being responsible for high losses in olive production (Medjkouh et al, 2018a). The fly attack significantly affects the fruit weight of different olive cultivars (Medjkouh et al, 2018b). Economopoulos et al, (1982) and Michelakis, (1990) reported that in Mediterranean countries, especially in Greece and in Italy, feeding activity of Olive fly larvae caused 30% yield losses.…”
Section: Discussionmentioning
confidence: 99%
“…Olive fly is the major olive pest in the Mediterranean Basin, being responsible for high losses in olive production (Medjkouh et al, 2018a). The fly attack significantly affects the fruit weight of different olive cultivars (Medjkouh et al, 2018b). Economopoulos et al, (1982) and Michelakis, (1990) reported that in Mediterranean countries, especially in Greece and in Italy, feeding activity of Olive fly larvae caused 30% yield losses.…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, fruit size and shell hardness has been found to influence the level of insect feeding damage. Feeding on physic nut by Leptoglossus zonatus resulted in larger fruits having more seed abortion and feeding resulted in more shriveled or damaged nuts [12]; similarly, some varieties of olives with larger fruits had a higher infestation rate by the olive fruit fly, Bactrocera oleae [32]. In hazelnut, shell thickness was not correlated with damage by brown marmorated stink bugs, Halyomorpha halys , and the authors suggested that shell thickness should not be a criterion to select cultivars resistant to H. halys [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the percent of shriveled kernels was higher in L. zonatus cages than controls in two varieties, Monterey and Carmel, while in 2015, the cages with L. zonatus resulted in higher levels of shriveled kernels in Nonpareil and Monterey. Research has similarly found that insect feeding damage varies among almond varieties as well as in varieties of other crops such as in apple, blueberry and olives [13,17,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Gómez-Caravaca et al, no clear correlation seems to exist between the percentages of fly attack and phenolic content [42]. Moreover, verbascoside, tyrosol and hydroxytyrosol were the compounds that were most adversely affected by B. oleae infestation, but the fly attack was significantly correlated with the weight of the fruits, but not with the phenolic compounds [43]. In fact, anthracnose disease causing more fruit damage than olive fly, and producing lipases that hydrolyze the acylglycerols releasing free fatty acids, can promote more differences in olive oil characteristics than olive fly, as observed in laboratory context studies [19].…”
Section: Health Claims Vs Olive Damage By Olive Fly and Anthracnose D...mentioning
confidence: 94%